Ireland : Report on Observance of Standards and Codes (ROSC). (IMF Staff Country Reports; Country Report ;, 2014)
This Report on Observance of Standards and Codes (ROSC) on Ireland highlights that the Central Bank of Ireland has made significant progress in implementing a proactive and intensive approach to supervision. The Probability Risk and Impact System, the backbone of the new risk-based supervisory approach, is intellectually appealing and significant progress was evident to the mission and recognized by market participants. The reform process is relatively young and effective implementation is still a work in progress that demands additional skills and resources. It is critical to maintain a clear direction and focus on implementation efforts, and that enforcement powers are used as a successful deterrent, including the new powers the Central Bank of Ireland was given under the Central Bank of Ireland Act 2013. The Central Bank of Ireland has set up sound foundations; however, gauging the full effectiveness of the reforms requires time for the new framework to season and for staff to gain experience through its use.